دور السيلكون والبورون وحمض السالسيليك في تحسين نوعية ثمار البرتقال أبو سرة. - سليمان, سوسن; أحمد, محمد; أحمد, بتول (Latakia University Journal -Biological Sciences Series, 2019)
The effect of foliar spray of Washington Navel Orange trees with Silicon (Si), Boron (B) and Salicylic acid (SA) on fruits quality: fruit size, V.C, TSS, TA, and total sugars were studied. The results showed that treatment with Salicylic (50 ppm) increased fruit size (360 cm3), vitamin C content (34.35 mg/100 ml) and TSS (15.6%). The results indicated as well, that treatment with Si (100 ppm) and its combination with Boron (Si 200 ppm+ B100 ppm) increased fruit acidity (1.18 and1.05 %) respectively, whereas, Si (100 ppm) + B (50 ppm) increased fruits total sugars (11.41%). تمت دراسة تأثير رش أشجار البرتقال (أبو سرة) بالسيليكون ( (Siعلى شكل (سيليكات الصوديوم) وحمض السالسيليك (SA) وحمض البوريك (B) في نوعية ثمار البرتقال من حيث حجمها ومحتواها من فيتامين C والمواد الصلبة الذائبة والحموضة وكذلك نسبة السكريات. أظهرت النتائج أن المعاملة بحمض الساليسيليك (50 ppm ) قد حققت أعلى زيادة في محتوى الثمار من فيتامين C (34.35 مغ/100 مل) و المواد الصلبة الذائبة TSS (15.6%)، وكذلك حجم الثمار (360 سم3). كما أظهرت أن المعاملة بالسيليكون (T1:100 ppm ) والمعاملة المشتركة للسيلكون (200 ppm ) والبورون (100 ppm(T9) إلى زيادة حموضة العصير (1.05 و 1.1% على التوالي)، في حين زادت المعاملة المشتركة للسيليكون (100 ppm ) والبورون(50 ppm )(T11) محتوى الثمار من السكريات الكلية (11.4%).